PEMANFAATAN ECENG GONDOK SEBAGAI CAMPURAN KONSENTRAT PAKAN PADA BUDIDAYA KAMBING DI DESA WANADADI KABUPATEN BANJARNEGARA - Bahrun, .; Ratnanigtyas, Nuniek Ina; Noorhidayah, Ratri; Herliana, Okti (Jurnal Dinamika Pengabdian, 2020)
The limitations of forage sources during the dry season and the high cost of manufacturing feeds are one of the obstacles faced by Menda Jaya goat breeders in Wanadadi Village. Water hyacinth is a water weed that can interfere with the quality of the waters of the Mrica Reservoir in the Regency of Banjarnegara. The management of water hyacinth is one of the efforts in the management of water resources and environment to maintain the sustainability of reservoir organizations. On the other hand this plant has several benefits and potential that are feasible to be developed, namely as animal feed ingredients because the protein content is quite high, so that it can be used as a substitute for factory feed for ruminants and poultry. This activity aimedto utilized water hyacinth as a conservation effort for reservoir waters and provide added value in the community, namely improving the community's skills in making concentrate animal feed with additional water hyacinth additives to support the goat breeding business. The method used in this community empowerment activity is the PRA (Participatory Rural Appraisal), which is the active participation of all people involved in this activity. Included activities: counseling and training on the use of water hyacinth as a mixture of concentrated ingredients for goat feed, doing demonstration plots for goat livestock experiments, assistance and evaluation. The results of the activity showed that goats are starting to adapt to feed concentrates with water hyacinth additives   Keywords: Goat, concentrate feed, eceng gondok.   ABSTRAK Keterbatasan hijauan sumber pakan pada saat musim kemarau dan mahalnya pakan pabrikan menjadi salah satu kendala yang dihadapi peternak kambing Menda Jaya di Desa Wanadadi. Eceng gondok merupakan gulma air yang dapat mengganggu kualitas perairan Waduk Mrica di Kabpupaten Banjarnegara. Penanggulangan eceng gondok merupakan salah satu upaya dalam manajemen sumber daya dan lingkungan perairan untuk menjaga kelestarian oraganisme parairan. Di sisi yang lain tanaman ini memiliki beberapa manfaat dan potensi yang layak untuk dikembangkan, yaitu sebagai bahan pakan ternak karena kandungan proteinnya cukup tinggi, sehingga dapat digunakan sebagai pengganti pakan pabrikan untuk ternak ruminansia maupun unggas. Kegiatan ini bertujuan untuk memanfaatkan eceng gondok menjadi usaha konservasi perairan waduk dan memberikan nilai tambah di masyarakat, yaitu meningkatkan ketrampilan masyarakat dalam pembuatan pakan ternak konsentrat dengan bahan tambahan eceng gondok guna mendukung usaha peternakan kambing. Metode yang digunakan dalam kegiatan pemberdayaan masyarakat ini adalah PRA (Partisipatory Rural Appraisal) yaitu peran serta aktif seluruh masyarakat yang terlibat dalam kegiatan ini. Meliputi kegiatan: penyuluhan dan pelatihan pemanfataan eceng gondok sebagai bahan campuran konsentrat pakan kambing, Pembuatan Demplot percobaan ternak kambing, pendampingan dan evaluasi. Hasil kegiatan menunjukkan ternak kambing mulai beradaptasi dengan pakan konsentrat dengan bahan tambahan eceng gondok.   Kata kunci: Ternak, kambing, konsentrat, eceng gondok.